Adaptive sliding mode current control with sliding mode disturbance observer for PMSM drives. (May 2019) - Deng, Yongting; Wang, Jianli; Li, Hongwen; Liu, Jing; Tian, Dapeng
Abstract: This paper focuses on the current control of a permanent magnet synchronous motor (PMSM) for electric drives with model uncertainties and external disturbances. To improve the performance of the PMSM current loop in terms of the speed of response, tracking accuracy, and robustness, a hybrid control strategy is proposed by combining the adaptive sliding mode control and sliding mode disturbance observer (SMDO). An adaptive law is introduced in the sliding mode current controller to improve the dynamic response speed of the current loop and robustness of the PMSM drive system to the existing parameter variations. The SMDO is used as a compensator to restrain the external disturbances and reduce the sliding mode control gains. Experiments results demonstrate that the proposed control strategy can guarantee strong anti-disturbance capability of the PMSM drive system with improved current and speed-tracking performance. Highlights: This paper proposes a current control strategy for the PMSM drives by combining the adaptive sliding mode control (ASMC) and sliding mode disturbance observer (SMDO). The ASMC is utilized to provide online compensation for disturbances caused by the PMSM model uncertainties. The SMDO is designed to estimate the external disturbances and add a corresponding feedback compensation item to the output of the ASMC current controller. The effectiveness of the proposed method is verified by experimental results.